Implementation of Educational Democracy in Learning to Form Student Character in High Schools - Sekar Kurnia Rahmadani; Firman; Dina Sukma (Aslim: Journal of Education and Islamic Studies, 2025)
Education is one of the basic human needs that must be met so that humans can be more respected and considered superior compared to people who do not receive education. This is because education has a more important purpose than simply ensuring human survival. Furthermore, education is a component that cannot be separated from a person in any way. Humans undergo a complete education process, which is influenced by their parents, culture, and environment, starting from when they are in the womb to adulthood and old age. To assess how educational democracy can be integrated into the learning process of students enrolled in secondary schools, the purpose of this study is to investigate the possibility of doing so. An approach known as a literature study was used in this study. This approach involves collecting data from websites, publications, and journals that can be accessed via the internet. The information is then subjected to qualitative analysis, which involves the use of various methodologies for data analysis during a process consisting of four stages: obtaining data, reducing data, presenting data, and drawing conclusions. As a result of these findings, students are currently not only used as objects of learning, but also used as subjects who are directly involved in the arguments that occur during the learning process. Thus, it is hoped that teachers can provide a democratic learning environment for their students.